2022
DOI: 10.31083/j.rcm2312400
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Simple Inflammatory Markers in Off Pump Surgery—Review

Abstract: The inflammatory background of coronary artery disease is gaining more attention in recent times. Off pump surgery is minimally invasive type of surgical revascularization with relatively low number of applications in cardiac surgery centers worldwide that allows for perioperative inflammatory reactions minimalization. The simple inflammatory markers (neutrophil to lymphocyte ratio (NLR), monocyte to lymphocyte ratio (MLR), platelets to lymphocyte ratio (PLR), systemic inflammatory index (SII), systemic inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 127 publications
(176 reference statements)
0
2
0
Order By: Relevance
“…A number of studies have demonstrated that the level of neutrophils, lymphocytes, and platelets plays an important role in the development of chronic inflammation and the progression of cardiovascular diseases. In some studies, biomarkers such as C-reactive protein, NLR, and PLR demonstrated their prognostic values for the risk of postoperative complications and mortality [ 15 , 16 , 17 ]. For example, in the study by Russu E. et al, the preoperative role of NLR and PLR in the medium-term outcome of patients surgically revascularized for femoropopliteal disease was studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that the level of neutrophils, lymphocytes, and platelets plays an important role in the development of chronic inflammation and the progression of cardiovascular diseases. In some studies, biomarkers such as C-reactive protein, NLR, and PLR demonstrated their prognostic values for the risk of postoperative complications and mortality [ 15 , 16 , 17 ]. For example, in the study by Russu E. et al, the preoperative role of NLR and PLR in the medium-term outcome of patients surgically revascularized for femoropopliteal disease was studied.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the possibility of using the SII as a predictor of unfavorable outcomes among patients with acquired heart defects was actively investigated. This marker of systemic inflammation takes into account the level of neutrophils, platelets, and lymphocytes, thereby reflecting both inflammatory and immunological activation, as well as activation of the coagulation cascade [ 17 ]. The SII was studied in patients with chronic heart failure, neoplasms, and nervous system disorders [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%